NASOLABIAL V-Y ADVANCEMENT FLAP - TWO APPLICATIONS, TWO COMPLEXITIES - Matos, Diogo (2015)
The V-Y advancement flap is perfectly adaptable to the nasolabial fold and is extremely useful in that location. Apart from its classic application as vertical advancement flap, multiple variants have been described. The authors describe two case reports with two different applications of this flap, which represent two different degrees of technical complexity. In the first case, a 64-year-old male has a left paranasal basal cell carcinoma that was excised, resulting in a 2 cm width surgical defect. The second case mentions a 61-year-old male with a basal cell carcinoma of the nasal ala, which excision resulted in a defect affecting the full-thickness of part of the nasal ala and the perialar portion of the nasolabial fold.The details of the surgical reconstructions by means of a nasolabial fold- centered V-Y advancement flap, in the first case, and a turnover advancement flap centered in the nasolabial fold, in the second case, will be discussed.